2022
DOI: 10.1128/mbio.00022-22
|View full text |Cite
|
Sign up to set email alerts
|

High-Definition DIC Imaging Uncovers Transient Stages of Pathogen Infection Cycles on the Surface of Human Adult Stem Cell-Derived Intestinal Epithelium

Abstract: Knowledge of dynamic niche-specific interactions between single microbes and host cells is essential to understand infectious disease progression. However, advances in this field have been hampered by the inherent conflict between the technical requirements for high-resolution live-cell imaging on the one hand and conditions that best mimic physiological infection niche parameters on the other.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 92 publications
1
34
0
Order By: Relevance
“…One interesting observation in this study is that Giardia cysts and encysting cell/trophozoite cell debris induce a very strong response in the Caco-2 cells and this can reflect that Giardia , even if it is mainly colonizing the duodenum, can give effects on host responses in the lower part of the intestinal region and this has been seen in earlier in vivo studies ( Cotton et al., 2014 ; Allain & Buret, 2020 ). New systems using non-transformed cells are needed in order to further study interactions between Giardia and host cells and the recent publication of two studies of Giardia -host cell interactions using enteroids derived from human intestinal stem cells show that this is on the way ( Holthaus et al., 2021 ; van Rijn et al., 2022 ). In these systems it will be important to include parasites or antigens from all life cycle stages of Giardia in order to get a complete picture of Giardia ’s molecular pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting observation in this study is that Giardia cysts and encysting cell/trophozoite cell debris induce a very strong response in the Caco-2 cells and this can reflect that Giardia , even if it is mainly colonizing the duodenum, can give effects on host responses in the lower part of the intestinal region and this has been seen in earlier in vivo studies ( Cotton et al., 2014 ; Allain & Buret, 2020 ). New systems using non-transformed cells are needed in order to further study interactions between Giardia and host cells and the recent publication of two studies of Giardia -host cell interactions using enteroids derived from human intestinal stem cells show that this is on the way ( Holthaus et al., 2021 ; van Rijn et al., 2022 ). In these systems it will be important to include parasites or antigens from all life cycle stages of Giardia in order to get a complete picture of Giardia ’s molecular pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on human intestinal organoids showed that STm induced pro-inflammatory gene expression and downregulation of genes associated with cell cycle and DNA repair affecting the host proliferation machinery ( Lawrence et al, 2021 ). Besides the 3D organoid model, 2D organoid monolayer model allow imaging of infection and interaction between IECs and STm as well as the importance of M cells providing an interesting tool to identify STm interaction with specific IEC ( Nickerson et al, 2021 ; van Rijn et al, 2022 ).…”
Section: Relevance Of Intestinal Epithelial Organoids To Decipher ...mentioning
confidence: 99%
“…Murine small intestinal enteroid cultures were thawed from previously established stocks (Hausmann et al, 2020), and maintained within Matrigel (Corning) domes overlaid with complete mouse IntestiCult (Stemcell), as detailed elsewhere (Samperio Ventayol et al, 2021). Enteroid-derived monolayers were established using an adapted version of a recently developed 3D-printed polylactide (PLA) transwell chamber, allowing a short working distance for dipping-objective microscopy (van Rijn et al, 2022).…”
Section: Murine Enteroid-derived Epithelial Monolayersmentioning
confidence: 99%